In search of graduate attributes: A survey of six flagship programmes - Winberg, C.; Staak, A.; Bester, M.; Sabata, S.; Scholtz, D.; Sebolao, R.; Monnapula-Mapesela, M.; Ronald, N.; Makua, M.; Snyman, J.; et al. (South African Journal of Higher Education, 2018)
The focus of this study is the emergence of distinctive graduate attributes in flagship programmes at Universities of Technology in South Africa. The theoretical framework chosen for this study, Legitimation Code Theory (Maton 2014), offers an explanation of the underlying knowledge principles that make different kinds of thinking, doing and being possible. This paper studies how favourable graduate attributes were achieved, identifies similarities across underpinning structures, and highlights the challenges faced by universities of technology in creating environments in which desired graduate attributes might be developed. The paper offers a means of understanding the potential for the emergence of graduate attributes across undergraduate programmes in vocational and professional higher education contexts.